Pengaruh Metode Diskusi Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas XI SMA Negeri 1 Pangururan Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Silaen, Bunga Kristina; Hulu, Adiani; Nababan, Damayanti (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
The purpose of this study is to determine the positive and significant influence of discussion methods on the learning activity of grade XI students of SMA Negeri 1 Pangururan, Samosir Regency for the 2023/2024 Learning Year. The method used in this study is quantitative research method. The population is all grade XI students of SMA Negeri 1 Pangururan, Samosir Regency for the 2023/2024 Learning Year who are Protestant Christians totaling 252 people and a sample of 50 people was determined, which is 20% of the total population using random sampling techniques. Data were collected using a positive closed questionnaire of 36 items, namely as many as 16 items for variable X and as many as 20 items for variable Y compiled by the author in accordance with expert theory. The results of the data analysis showed that there was an influence of the discussion method on the learning activity of class XI Christian education SMA Negeri 1 Pangururan, Samosir Regency Learning Year 2023/2024: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0,572 > rtable(=0,05,n=50) = 0,297. b) Test the relationship of significant obtained values tcount= 4,831 > ttable(=0,05,dk=n-2=48)= 2,021. 2) Test the influence: a) Test the regression equation, obtained regression equation . b) Regression coefficient of determination test (r2) = 32,7%. 3) Test the hypothesis using the F test obtained Fcount > Ftable=(=0,05,dk numerator k=16,dk denominator=n-2=50-2=48) is 23,34 > 1,51. Thus, Ha, namely the influence of the discussion method on the learning activity of class XI Christian education of SMA Negeri 1 Pangururan, Samosir Regency Learning Year 2023/2024 was accepted and H0 was rejected.